A VALUE-ADDED ANALYSIS OF THE PEMPEK BUSINESS IN TENGGARONG, INDONESIA - Gusti Haqiqiansyah; Juliani; Said Abdusysyahid; Muhammad Syafril; Nurul Ovia Oktawati; Etik Sulistiowati Ningsih; Erwan Sulistianto (PT. Jurnal Center Indonesia Publisher, 2025)
The processing of fisheries products, characterized by the diversification of processed goods, presents a promising avenue for entrepreneurial endeavors. Product diversification holds the potential to augment the intrinsic value of products and concurrently elevate public consumption of fisheries-related commodities. This research aims to analyze the prospective added value stemming from the pempek businesses in Melayu Sub-District, Tenggarong, Kutai Kertanegara. The acquired data underwent meticulous processing, tabulation, and subsequent analytical examination, characterized by both descriptive and value-added analyses, utilizing the Hayami model. The research showed that the managed pempek businesses are predominantly of small scale, utilizing relatively simple technology. On average, a single production cycle yields 126.64 kg, or monthly output of 633.2 kg. The value-added analysis reveals a figure of 186,734 IDR per kg, with a commendable value-added ratio of 70.95%. This signifies that the conversion of belida fish into pempek not only imparts substantial value but also presents a highly promising avenue for further expansion and development.